2004
DOI: 10.1007/s00403-004-0475-2
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-regulated expression of Toll-like receptors 2 and 4 in HaCaT keratinocytes

Abstract: Toll-like receptors (TLRs) play an important role in the recognition of pathogens in keratinocytes. In this study, we investigated whether the differentiation state of HaCaT keratinocytes correlates with the expression of TLR2 and TLR4 genes. The expression levels of TLR2 and TLR4 in a HaCaT differentiation model system were determined using quantitative real-time RT-PCR (Q-RT-PCR) and flow cytometry. The progression of keratinocyte differentiation was monitored by determining the level of involucrin gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 27 publications
5
35
1
2
Order By: Relevance
“…1A), as previously observed on other keratinocyte cell lines and primary keratinocytes (17,18). An intense production of DEFB2, assessed by PCR and immunofluorescence analysis, was observed when cells were stimulated with the TLR2-and TLR4-specific bacterial ligands PGN and LPS, respectively, for 18 h (Fig.…”
Section: Human Keratinocytes Produce ␤-Defensin 2 In Response To the supporting
confidence: 85%
“…1A), as previously observed on other keratinocyte cell lines and primary keratinocytes (17,18). An intense production of DEFB2, assessed by PCR and immunofluorescence analysis, was observed when cells were stimulated with the TLR2-and TLR4-specific bacterial ligands PGN and LPS, respectively, for 18 h (Fig.…”
Section: Human Keratinocytes Produce ␤-Defensin 2 In Response To the supporting
confidence: 85%
“…This result contradicts the previous study in HaCaT cells that reported differences in TLR2 and TLR4 mRNA levels between undifferentiated and differentiated keratinocytes (Pivarcsi, Koreck et al 2004). This may be because HaCaT cell lines are immortalized keratinocytes obtained from adult skin, whilst the differentiation studies in this chapter were performed using primary keratinocytes from neonatal skin.…”
Section: The Differentiation Status Of Keratinocytes Does Not Affect contrasting
confidence: 99%
“…A previous study in HaCaT cells showed that TLR2 and TLR4 mRNA was upregulated during keratinocyte differentiation (Pivarcsi, Koreck et al 2004). Cell surface expression of TLR2 and TLR4 also increased.…”
Section: The Differentiation Status Of Keratinocytes Does Not Affect mentioning
confidence: 93%
“…Cytokines, chemokines, and antimicrobial peptides produced by epithelial cells enable them to participate in innate and acquired immune responses (1)(2)(3)(4)(5)(6). In addition, epithelia express certain TLRs, which may contribute to their ability to sense and respond to invading pathogens (3,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%